Explaining Webrooming Intention through Extended TAM and TPB: Insights from Gen Y and Z Travelers - Octaviani, Natasya; Yudhistira, Putu Gde Arie (Universitas Airlangga, 2026)
Objective: This study investigates the determinants of webrooming intention among Generation Y and Z travelers by integrating the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), extended with need for interaction and online perceived risk. Design/Methods/Approach: Using data from 479 travelers, the study applies Partial Least Squares Structural Equation Modeling (PLS-SEM) and Necessary Condition Analysis (NCA) to examine both sufficient and essential conditions that shape webrooming intention. Findings: Perceived usefulness of online search, attitude, subjective norm, perceived behavioral control, and need for interaction significantly drive travelers’ webrooming intention, while perceived ease of online search indirectly affects intention through attitude. The NCA findings indicate that perceived usefulness and subjective norm serve as small but significant necessary conditions. Originality/Value: This study contributes to the existing literature on multichannel consumer behavior by integrating TAM and TPB with interactional and risk-related constructs that explain webrooming decisions among Gen Y and Gen Z travelers. It further advances the literature by being the first to combine PLS-SEM and NCA to examine webrooming intention in the tourism context. Practical/Policy implication: Tourism businesses should enhance the usefulness and credibility of online information, strengthen offline reassurance through personal interaction, and design integrated online–offline strategies that support travelers’ multichannel decision-making.